Formulation and Organoleptic Evaluation of Roselle (Hibiscus sabdariffa) Jamu Godog with Stability and Microbial Quality Assessment - Irianto, Iramie Duma Kencana; Purwanto; Nurhaeni, Farisya; Ana Mardiyaningsih; Bangkit Ary Pratama; Fiqoh, Latifah Nisa; Febriana Ardiyanti (Journal of Fundamental and Applied Pharmaceutical Science, 2025)
Jamu is a traditional medicinal preparation proven to have many pharmacological properties and is widely used in Indonesian society. Unfortunately, many people do not like herbal medicine because of its unpleasant taste and odor. This phenomenon has driven much research in modifying the organoleptic parameters of jamu to make it more acceptable to the tongues and noses of consumers while still having a potent effect on health. This study, thus, aimed to formulate a roselle (Hibiscus sabdariffa)-enhanced jamu godog (traditional Indonesian herbal decoction) and evaluate its organoleptic properties, physical stability, and microbial quality. Jamu godog was prepared by sequentially boiling and mixing ground ginger, turmeric, lemongrass, roselle, rock sugar, and lime, with roselle concentrations set at 0%, 0.3%, and 0.6%. Organoleptic attributes and pH stability were assessed before and after storage at 4°C and 25°C for seven days. Microbial contamination was measured via total plate count (TPC) after storage at 4°C for three and seven days. A hedonic test with 40 participants across two age groups evaluated sensory acceptance. Results indicate that the addition of roselle at 0.3% concentration optimized taste and overall acceptability while maintaining pH stability and microbial safety within BPOM standards throughout the storage period. This formulation demonstrates potential as a palatable and microbiologically safe herbal preparation with enhanced consumer acceptance.